ANALISIS SEKTOR PROGRESIF DAN KOMODITI BASIS PERTANIAN DI KABUPATEN BOLAANG MONGONDOW, PROVINSI SULAWESI UTARA - Siswono Rahmat Yunus; Nurdin Lanuhu; Pipi Dian Sari (Jurnal Sosial Ekonomi Pertanian, 2020)
AbstractThis study aims to: 1) Identify the economic sectors included in the progressive sector in Bolaang Mongondow Regency; 2) Identify agricultural commodities that are commodity-based agriculture in Bolaang Mongondow Regency. This study uses primary data from the Department of Agriculture and Plantation Agency and secondary data in the form of data on Gross Regional Domestic Product (GRDP) of Bolaang Mongondow Regency and North Sulawesi Province in 2013-2017 and agricultural commodity data of Bolaang Mongondow Regency and North Sulawesi Province in 2012-2016. The data was analyzed using the Location Quotient and Shift Share methods. The results of the study concluded that: 1) There are 5 economic sectors which are the base sectors namely the Agriculture, Forestry and Fisheries sector; Mining and Excavation sector; the Electricity and Gas Procurement sector, the Real Estate sector and the Education Services sector. However, only the Mining and Excavation sector has a progressive growth rate and has a competitive advantage. As for the Agriculture sector itself, it has a growth rate that is not progressive and lacks competitive advantage; 2) There are 15 agricultural commodities which are the base commodities in Bolaang Mongondow Regency, namely green beans, soybeans, corn, rice, candlenut, coffee, cocoa, pineapple, mango, mangosteen, spinach, long beans, kale, eggplant and potatoes. As for now the commodities that are the government's main focus are soybeans, corn, rice, cocoa, pineapple and potatoes. Keywords: Progressive Sector; Base Commodity; Location Quotient; Shift Share.